Postoperative Lower Esophageal Dilation in Children Following the Performance of Nissen Fundoplication - Schneider, Anne; Gottrand, Frédéric; Sfeir, Rony; Duhamel, Alain; Bonnevalle, Michel; Guimber, Dominique; Michaud, Laurent (European Journal of Pediatric Surgery, 2012)
Objectives The purpose of this study is to study the frequency and factors associated with lower esophageal dilation (LED) after Nissen fundoplication.Methods This retrospective monocentric study included 288 patients who had undergone Nissen fundoplication from 1998 to 2009. The frequency of children requiring LED was assessed. The clinical characteristics of the patients at the time of fundoplication, their symptoms, and outcomes were recorded. The population with LED (group 1) was compared with the population without LED (group 2) to identify factors associated with postfundoplication LED using multivariate analysis.Results LED was required by 70 patients (24%) because of postoperative dysphagia, and 45/70 were dilated within the first 6 months. The mean age at dilation was 72 months (standard deviation [SD] 65), with an average post-Nissen delay of 9 months (SD 13). Surgical revision was required by 11 patients because of LED failure (n = 10) or postdilation perforation (n = 1). Patients who required post-Nissen dilation were significantly more frequently fed orally than those in group 2 and had more postoperative complications (dumping syndrome, surgical revision).Conclusions A significant frequency of postfundoplication LED was observed in this pediatric population. Dilation was associated in children with preoperative feeding or postoperative complications (dumping syndrome, surgical revision).
Keywords: Nissen fundoplication; lower esophageal dilation; persistent dysphagia